Pemanfaatan Grup Chat Whatsapp dalam Komunikasi Koordinasi Mahasiswa Universitas Sains Indonesia - Vania, Vania Utamie Subiakto; Cucu Khodijah; Elis Yulianti (Journal of Islamic Studies & Social Science, 2025)
The development of digital communication technology has changed the pattern of interaction in student academic life. One of the platforms used to support communication and coordination is the WhatsApp instant messaging application, especially the chat group features. This study aims to examine how Indonesian University of Science University students use the WhatsApp group as a means of coordinative communication in academic activities, as well as identifying the obstacles and strategies used in the process. The method used is a qualitative approach with data collection techniques in the form of in -depth interviews and participatory observations of a number of student WhatsApp groups, both class, organization, and committee. The results showed that the WhatsApp group played an important role in delivering information, division of tasks, decision making, and reminder of schedules and deadlines. However, the effectiveness of coordination communication is often disrupted by several obstacles, including overloading information, lack of active member participation, and the potential for miscommunication due to the delivery of unclear messages. To overcome this, students make various efforts such as establishing communication rules in the group, appointing active admins, using structured message formats, and utilizing additional features such as message embedding and integration with other applications. This study concluded that the strategic use of the WhatsApp group can improve the efficiency of students' coordinative communication, but still requires digital literacy and orderly communication culture.